Camaraderie Reincorporated: Tough Mudder and the Extended Distribution of the Social. (December 2015) - Weedon, Gavin
Tough Mudder, a market-leading event in the burgeoning practice and industry of mud running, is a 21 km "military-style" obstacle course with a curiously collaborative ethic. Teams of runners traverse the course in the name of fun, fitness, bravado, and much more besides, galvanized around Tough Mudder's distinctive ethos of togetherness. This essay sets out to reassemble the "camaraderie" for which Tough Mudder is renowned as an element and outcome of material, corporeal, and symbolic enactments, and, with actor-network theory as a guiding sensibility, recasts it as a profoundly shared endeavor, one in which a whole host of actors, human and otherwise, make dramatic and subtle contributions.